2011
DOI: 10.1177/1524838010386975
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Childhood Maltreatment and Self-Injury: A Review of the Literature on Conceptualization and Intervention

Abstract: The following article reviews literature pertaining to the association between child maltreatment and self-injury and the ways it varies according to maltreatment type. Research supporting various mediators of the relations between different maltreatment types and self-injury is summarized. Informing mediator models, dominant theories of functionality, particularly affect regulation theories, are summarized and granted empirical support. Following from explanations of its functionality, three developmental pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 80 publications
5
74
1
1
Order By: Relevance
“…Although research related to the impact of physical and sexual maltreatment on children and youth and its potential relation to the development of NSSI has been widely studied (Ford and Gó-mez, 2015;Moyer, 2008: Lang andSharma-Patel, 2011), there is a paucity of research on the impact of witnessing domestic violence in its relation to NSSI. This is despite widespread evidence that witnessing domestic violence carries with it numerous significant consequences for the adjustment of child, including mental health and behavioral problems, as well as an increased risk for the expression of violence by those same young people (for a comprehensive overview of the literature to date see Artz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research related to the impact of physical and sexual maltreatment on children and youth and its potential relation to the development of NSSI has been widely studied (Ford and Gó-mez, 2015;Moyer, 2008: Lang andSharma-Patel, 2011), there is a paucity of research on the impact of witnessing domestic violence in its relation to NSSI. This is despite widespread evidence that witnessing domestic violence carries with it numerous significant consequences for the adjustment of child, including mental health and behavioral problems, as well as an increased risk for the expression of violence by those same young people (for a comprehensive overview of the literature to date see Artz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, childhood physical abuse has been associated with NSSI in some studies (Heath et al, 2009;Gonçalves et al, 2015;Wan et al, 2015) but not in others (Auerbach et al;Rabinovitch et al, 2015). Even fewer studies have examined the effects of emotional abuse and neglect but what little evidence is available has suggested a significant association with NSSI (for a review see Lang and Sharma-Patel, 2011).…”
mentioning
confidence: 99%
“…Furthermore, Maniglio (2010Maniglio ( , 2012 conducted systematic reviews and found that having a history of childhood sexual abuse was a significant risk factor for developing both depression and anxiety disorder, regardless of gender of the victim and severity of the abuse. With respect to the association between ACEs and NSSI, various systematic reviews and meta-analyses (Ford & Gómez, 2015;Lang & Sharma-Patel, 2011;Maniglio, 2011;Smith, Kouros, & Meuret, 2014) have shown that adolescents with a history of ACEs are more likely to engage in NSSI, even after adjusting for demographic and known mental health factors. Similar results have been found among adolescent inpatients (e.g., Bifulco et al, 2014;Kaess et al, 2013;Thomassin et al, 2016).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…In abusive contexts, some young people may selfinjure in an attempt to avoid punishment or abuse (Lang 2011).…”
Section: Release From a Predicament (And Associations With Present Ormentioning
confidence: 99%